2013
DOI: 10.1186/1475-2875-12-313
|View full text |Cite
|
Sign up to set email alerts
|

Malaria indicator surveys demonstrate a markedly lower prevalence of malaria in large cities of sub-Saharan Africa

Abstract: BackgroundOne in eight sub-Saharan Africans now lives in a city with a population greater than 750,000. Decision makers require additional evidence regarding the burden of malaria in these large cities. This paper presents results from analysis of existing data from nationwide household surveys measuring malaria parasitaemia by microscopy among children six to 59 months of age in 15 countries of sub-Saharan Africa.MethodsGeo-coordinates for each survey cluster were used to determine the distance from the clust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 34 publications
6
16
0
Order By: Relevance
“…funestus mosquitoes from an urban site. 20 This study also supports the findings of the 2010 Demographic and Health Survey (DHS), 21 those reported generally from several major cities in sub-Saharan Africa, 11,22 as well as the findings of Mathanga and others, 9,23 who demonstrated that malaria cases in urban Blantyre were more likely to have a history of recent travel to rural areas. It was not surprising to observe that anophelines were present in the study area at very low densities of 10.3% and 12.4% in 2008 and 2010, respectively.…”
Section: Discussionsupporting
confidence: 78%
“…funestus mosquitoes from an urban site. 20 This study also supports the findings of the 2010 Demographic and Health Survey (DHS), 21 those reported generally from several major cities in sub-Saharan Africa, 11,22 as well as the findings of Mathanga and others, 9,23 who demonstrated that malaria cases in urban Blantyre were more likely to have a history of recent travel to rural areas. It was not surprising to observe that anophelines were present in the study area at very low densities of 10.3% and 12.4% in 2008 and 2010, respectively.…”
Section: Discussionsupporting
confidence: 78%
“…In some rural settings, prevalence as high as 74% and 71.4% have been reported [9,20]. Thus, while evidence abound on malaria prevalence in urban areas, prevalence is generally lower than rural areas [11,21]. This lower malaria prevalence in urban areas could be as a result of better access to health facilities, well-designed houses that can protect against mosquito vectors, improved basic amenities and reduced mosquito breeding sites [22].…”
Section: Discussionmentioning
confidence: 99%
“…Urban areas generally have fewer mosquito breeding sites, better access to treatment and higher intervention coverage levels than rural areas [ 6 , 7 ]. Urbanization also involves significant ecological change and socio-economic change, including improved health, housing and wealth factors that impel significant entomological, parasitological and behavioural effects that generally reduce malaria transmission [ 2 , 4 , 5 ] and many malaria-endemic nations have recorded reduced malaria transmission in major cities [ 2 , 8 ]. Previous studies on the impact of ‘urbanicity’ have generally looked at malaria parasite prevalence over large scales or at specific metrics at small scales, and using a single indicator of urbanicity [ 9 ].…”
Section: Introductionmentioning
confidence: 99%